(3TQM GdCSHGH hGdYdGeGJ aj GdCeQGV heYGdLJgGs - (3fajS Hf YhV Hf Mcje, HYO (B841(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfCeG HYO ajbhd fajS Hf YhV Mcje GdWHjH Cfj bO cfJ aj Cgd HjJ eTghQjf HgPg GdUfGYIhcGf bSe GdCeQGV GdLRFjI ef gPG Gdaf de jJUO CMO ef GdCaGVd Edi GdBf dJaSjQgeeG ChQOg GdEeGe HbQGWaCQOJ Cf CcTa Yf hLhg ahGFO gPG GdbSes
(3BNQgG (B:s
(3hCf JYJUQ Ydi eKd LhR GdSQh hGdCHgd hSGFQ eG faY aj VeGO GdaJb aEfgG JTO GdYVh hJbTa GdQWhHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 44s
(3eYLe GdeDdajf(B: 4 / 39s
(3cTa GdXfhf(B: 1 / 77s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdWHs